The Role of Monetary Policy Uncertainty in Corporate Decisions (American Journal of Management, 2021)
The paper emphasizes the role of monetary policy uncertainty in understanding the common dynamics in corporate behavior. Building on common statistical properties of the corporate events, we extract the common pattern (factor) and the common variance (volatility) from five corporate event waves. Using the extracted common factor and the common volatility, this study examines the effect of monetary policy uncertainty on corporate decisions. We hypothesize and explore this explanation of how commonalities between the corporate event waves are formed. The Fed’s actions can result in higher monetary policy uncertainty, which can increase the uncertainty about the outcomes of the major firm activities. The findings from the econometric analyses suggest that monetary policy uncertainty has a significant influence on the dynamics of corporate event waves.
Keywords: management; corporate events; economic policy uncertainty; factor analysis; Bayesian estimation